Transparent microcrystalline glass as well as preparation method and application thereof
By controlling the proportion and grain size of the secondary crystal phase in the microcrystalline glass, and using components such as sodium sulfate and sacrystalline to perform nucleation and crystallization, the problem of insufficient optical performance of microcrystalline glass is solved, and the problem of insufficient optical performance of microcrystalline glass is realized. High transparency and low haze effects.
Patent Information
- Application Number
- CN202411454638.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-14
AI Technical Summary
Existing microcrystalline glasses have insufficient transparency and scattering characteristics in terms of optical performance, making it difficult to meet the needs of optical devices and displays.
By controlling the mass proportion and average grain size of the secondary crystal phase in transparent microcrystalline glass, nucleation and crystallization are carried out by combining sodium sulfate and silaxate as the main crystal phase, sodium silicate and zirconia as the secondary crystal phase, nucleation and crystallization are carried out by combining sodium sulfate and zirconia as the secondary crystal phase. Processing, optimize optical performance.
The average transmittance of light in the wavelength range of 400 to 780 nm is achieved with an average transmittance of more than 88% and a haze of less than 0.15, and has excellent optical performance.
Smart Images

Figure CN119306398A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of glass materials, and in particular to a transparent microcrystalline glass and a preparation method and application thereof. Background Art
[0002] As a composite material composed of amorphous and microcrystalline states, glass-ceramics has shown broad application prospects in the fields of optics, electronics, biomedicine, etc. due to its unique physical and chemical properties. The optical properties of glass-ceramics, such as transparency, refractive index, and scattering characteristics, directly determine its application effects in optical devices, displays, optical fiber communications, and other fields.
[0003] Therefore, it is very necessary to develop transparent microcrystalline glass with good optical properties to meet the needs of different fields. Summary of the invention
[0004] Based on the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a transparent microcrystalline glass with good optical properties and a preparation method and application thereof.
[0005] The technical solution of the present invention is as follows:
[0006] In a first aspect of the present invention, a transparent glass-ceramic is provided, wherein the crystal phase of the transparent glass-ceramic includes a main crystal phase and a secondary crystal phase, the mass proportion of the secondary crystal phase in the transparent glass-ceramic is greater than or equal to 0% and less than or equal to 8%; the average grain size of the secondary crystal phase is less than or equal to 10nm; the main crystal phase includes sodium nepheline and triclinic nepheline, and the secondary crystal phase includes sodium silicate and zirconium oxide; the total crystallinity of the transparent glass-ceramic is greater than or equal to 20%; in the transparent glass-ceramic, the average grain size of the crystal phase is greater than 10nm and less than or equal to 75nm;
[0007] When the thickness of the transparent microcrystalline glass is less than or equal to 1.0 mm, the average transmittance of the transparent microcrystalline glass for light in the wavelength range of 400 to 780 nm is greater than or equal to 88%, and the haze of the transparent microcrystalline glass is less than or equal to 0.15.
[0008] Optionally, in the transparent glass-ceramics, the mass proportion of sodium nepheline in the crystal phase is greater than 50%, and the total crystallinity of the transparent glass-ceramics is greater than or equal to 40% and less than or equal to 80%.
[0009] Optionally, in the transparent glass-ceramics, the mass proportion of triclinic pyroxene in the crystal phase is greater than 50%, and the total crystallinity of the transparent glass-ceramics is greater than 20% and less than or equal to 50%.
[0010] Optionally, the transparent glass-ceramics includes the following components in molar percentage:
[0011] SiO2 42%~65%,Al 2 O 3 10%~25%, Na 2 O 12%~25%, Li 2 O 1%~12%, MgO0%~3%, ZrO 2 0%~3%, B 2 O 3 0.5%~6%, P 2 O 5 0.5%~3%, TiO 2 0%~2%, clarifier 0.1%~2%; and the sum of the molar percentages of each component is 100%.
[0012] Optionally, the fining agent includes SnO 2 , NaCl and Sb 2 O 3 At least one of .
[0013] A second aspect of the present invention provides a method for preparing the transparent microcrystalline glass as described above, comprising the following steps:
[0014] Mixing ingredients according to the components of transparent glass-ceramics to obtain a mixed material;
[0015] After the mixture is melted, it is molded and annealed to obtain basic glass;
[0016] The base glass is subjected to a nucleation treatment and a crystallization treatment in sequence to obtain the transparent micro-ceramic glass;
[0017] Wherein, the transparent microcrystalline glass comprises the following components in terms of molar percentage:
[0018] SiO 2 42%~65%,Al 2 O 3 10%~25%, Na 2 O 12%~25%, Li 2 O 1%~12%, MgO0%~3%, ZrO 2 0%~3%, B 2 O 3 0.5%~6%, P 2 O 5 0.5%~3%, TiO 2 0%~2%, clarifier 0.1%~2%; and the sum of the molar percentages of each component is 100%.
[0019] Optionally, the temperature of the nucleation treatment is 500-600° C., and the time of the nucleation treatment is 30-480 min.
[0020] Optionally, the temperature of the crystallization treatment is 580-740° C., and the time of the crystallization treatment is 10-240 min.
[0021] Optionally, the forming method includes one of overflow down-draw method, float method, casting method or roller pressing method;
[0022] The annealing temperature is 420-480° C., and the annealing time is 6-24 hours.
[0023] A third aspect of the present invention provides an application of the transparent microcrystalline glass as described above in consumer electronic products.
[0024] Beneficial effect: The present invention can optimize the optical properties of microcrystalline glass by controlling the mass proportion of the secondary crystalline phase in the transparent microcrystalline glass to be greater than or equal to 0% and less than or equal to 8%, and the average grain size to be less than or equal to 10nm, so that the haze of the provided transparent microcrystalline glass (when the thickness is ≤1.0mm) is less than or equal to 0.15, the absolute value of the B value in LAB is between 0.6 and 1.0, and the average transmittance of light in the wavelength range of 400 to 780nm is greater than or equal to 88%, and has good optical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 1 and 2 are X-ray diffraction patterns of the transparent glass-ceramics prepared in Example 1 and Comparative Example 1.
[0026] Figure 2 Graph showing the transmittance of the transparent glass-ceramics prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0027] The present invention provides a transparent microcrystalline glass and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0028] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0029] Some of the terms in this invention are explained as follows:
[0030] Basic glass: A compound containing a variety of oxides (including silicon dioxide, aluminum oxide, sodium oxide, calcium oxide, etc.) is uniformly mixed, melted at high temperature, and then formed by one of the molding methods such as float method, overflow down-draw method, roller pressing method, and casting method, and annealed, and the glass is not nucleated, crystallized, or ion exchange chemically strengthened.
[0031] Glass-ceramics: A type of solid composite material that contains both a glass phase and a crystal phase (microcrystalline phase, crystalline phase) and is prepared by subjecting base glass to a targeted controlled crystallization treatment.
[0032] Nucleation: The base glass is heat treated to make the nucleating material in the glass grow tiny crystal nuclei.
[0033] Crystallization: The base glass is grown into a certain crystal based on the crystal nucleus through heat treatment.
[0034] Crystalline phase: It is the microscopic structure of crystals and is a general term for parts composed of a large number of crystalline solid phases.
[0035] Crystallinity: It is used to indicate the proportion of the crystallized area in the microcrystalline glass, generally the volume ratio of the crystal phase in the entire microcrystalline glass.
[0036] Main crystalline phase: It is the mineral phase that constitutes the main structure of the material, with a higher melting point and better high-temperature stability. In glass-ceramics, the type, quantity, distribution and defect status of the main crystalline phase directly determine its performance.
[0037] Secondary crystalline phase: It is a second phase distributed between the main crystalline phases. It is usually distributed between the main crystalline phases and is a manifestation of the increased degree of direct bonding of the crystalline phases in the material. In microcrystalline glass, the nature, quantity and distribution of the secondary crystalline phase will also affect the performance of the material. Generally, the content of the secondary crystalline phase is lower than that of the main crystalline phase.
[0038] Glass phase: It is an amorphous mineral phase with low refractoriness. It is in glass phase at room temperature, gradually softens during heating, and finally becomes liquid phase. The glass phase alone or together with some crystalline minerals fills the main crystal phase to form the material matrix, also known as the binding phase.
[0039] Transmittance: The ratio of the radiant energy that is projected and passes through an object to the total radiant energy that is projected onto the object during the process of the incident light flux leaving from the illuminated surface or the incident surface of the medium to the other side.
[0040] Haze: A beam of parallel light from standard light source C is irradiated vertically onto a transparent or translucent film, sheet or plate. Due to scattering inside and on the surface of the material, part of the parallel light deviates from the incident direction by more than 2.5°. The percentage of the scattered light flux Td to the light flux T2 that passes through the material is an important parameter for the optical transparency of transparent or translucent materials.
[0041] LAB value: L represents brightness, A includes colors from dark green to gray to bright pink, and B includes colors from bright blue to gray to yellow. The B value in LAB can represent the deviation of an object between yellow and blue.
[0042] Factors that affect the optical properties of glass-ceramics include the type of crystal phase, the proportion of each crystal phase, and the size of the crystal. First, different crystal types have different optical properties. Since light passes through the glass-ceramics through both the glass phase and the crystal phase, and the refractive index of the crystal phase is different from that of the glass phase, if the refractive index difference between the two is large, Rayleigh scattering will occur, resulting in changes in the optical properties of the glass-ceramics. Secondly, the crystal size is one of the important parameters of the microstructure of glass-ceramics, and it has a significant effect on the optical properties of glass-ceramics. The crystal size is closely related to the scattering properties of light. Smaller crystal size can reduce the scattering of light and improve the transparency of glass-ceramics. However, too small a crystal size may also lead to a decrease in crystallinity and affect other properties of glass-ceramics. Therefore, when preparing glass-ceramics, it is necessary to reasonably control the crystal size to balance the relationship between its optical properties and other properties. Finally, the proportion of the crystal phase in glass-ceramics reflects the relative proportion of the crystal phase to the amorphous phase in glass-ceramics, which also has an important influence on the optical properties of glass-ceramics. Too high a crystalline phase ratio may increase light scattering and reduce transparency, while too low a crystalline phase ratio may cause the microcrystalline glass to lose its unique performance advantages. Therefore, how to accurately control the crystalline phase ratio, especially the ratio of the secondary crystalline phase that accounts for ≤10% of the microcrystalline glass, the average grain size and other parameters, in order to optimize the optical properties of the microcrystalline glass, is an urgent problem to be solved in the current technical field.
[0043] Based on this, an embodiment of the present invention provides a transparent microcrystalline glass, wherein the crystal phase of the transparent microcrystalline glass includes a main crystal phase and a secondary crystal phase, and the mass proportion of the secondary crystal phase in the transparent microcrystalline glass is greater than or equal to 0% and less than or equal to 8%; the average grain size of the secondary crystal phase is less than or equal to 10nm; the main crystal phase includes sodium nepheline and triclinic nepheline, and the secondary crystal phase includes sodium silicate and zirconium oxide; the total crystallinity of the transparent microcrystalline glass is greater than or equal to 20%; in the transparent microcrystalline glass, the average grain size of the crystal phase is greater than 10nm and less than or equal to 75nm; when the thickness of the transparent microcrystalline glass is less than or equal to 1.0mm, the average transmittance of the transparent microcrystalline glass for light in the wavelength range of 400~780nm is greater than or equal to 88% (that is, for light in the wavelength range of 400~780nm, the average transmittance of the transparent microcrystalline glass is greater than or equal to 88%), the haze of the transparent microcrystalline glass is less than or equal to 0.15, the absolute value of the B value in LAB is between 0.6 and 1.0, and it has excellent optical properties.
[0044] In some embodiments, in the transparent glass-ceramics, the mass proportion of sodium nepheline in the crystal phase is greater than 50%, and the total crystallinity of the transparent glass-ceramics is greater than or equal to 40% and less than or equal to 80%. When the thickness of the transparent glass-ceramics is less than or equal to 1.0 mm, the haze of the transparent glass-ceramics is less than or equal to 0.15, and for light in the wavelength range of 400 to 780 nm, the transmittance of the transparent glass-ceramics is greater than or equal to 90%.
[0045] In some embodiments, in the transparent glass-ceramics, the mass proportion of triclinic nepheline in the crystal phase is greater than 50%, and the total crystallinity of the transparent glass-ceramics is greater than 20% and less than or equal to 50%. When the thickness of the transparent glass-ceramics is less than or equal to 1.0 mm, the haze of the transparent glass-ceramics is less than or equal to 0.12, and for light in the wavelength range of 400 to 780 nm, the transmittance of the transparent glass-ceramics is greater than or equal to 91%.
[0046] In some embodiments, in the transparent glass-ceramics, the average grain size of the crystalline phase is greater than 15 nm and less than or equal to 70 nm; in some embodiments, in the transparent glass-ceramics, the average grain size of the crystalline phase is greater than 20 nm and less than or equal to 65 nm.
[0047] In some embodiments, the mass proportion of the secondary crystalline phase in the transparent glass-ceramics is greater than or equal to 0% and less than or equal to 5%; in some specific embodiments, the mass proportion of the secondary crystalline phase in the transparent glass-ceramics is greater than or equal to 0% and less than or equal to 2%.
[0048] In some embodiments, the transparent glass-ceramics includes the following components, measured in mole percentage:
[0049] SiO 2 42%~65%,Al 2 O 3 10%~25%, Na 2 O 12%~25%, Li 2 O 1%~12%, MgO0%~3%, ZrO 2 0%~3%, B 2 O 3 0.5%~6%, P 2 O 5 0.5%~3%, TiO 2 0% to 2% and 0.1% to 2% of clarifier; and the sum of the molar percentages of each component is 100%. In some specific embodiments, the clarifier includes SnO 2 , NaCl and Sb 2 O 3 At least one of .
[0050] In this embodiment, SiO 2 As one of the main components of the network oxide of basic glass and microcrystalline glass, it is one of the important components that constitute the Si-O tetrahedron in the main body and form the network structure. 2 The molar content is 42% to 65%, for example, SiO 2 The molar content is 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65% or any value in a numerical range consisting of any two of the above numerical values as endpoints, preferably 44% to 60%.
[0051] Al 2 O 3 It is an intermediate oxide in the formation of glass-ceramics and the main component of sodium nepheline, triclinic nepheline and other crystal forms. It can significantly improve the thermal stability of basic glass and glass-ceramics. At the same time, due to [AlO 4 ] than [SiO 4 ] has a large volume, which can provide more space for ion exchange. Therefore, Al 2 O 3 It can promote ion exchange. 2 O 3 It will increase the viscosity of the glass, which is not conducive to melting. 2 O 3 The molar content is 10% to 25%, for example, Al 2 O 3 The molar content is 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value in a numerical range consisting of any two of the above numerical values as endpoints. Preferably, it is 12% to 23%.
[0052] Na 2 O is one of the main components of sodium nepheline, triclinic nepheline, sodium silicate and other crystal forms, and is also an important element in the subsequent chemical strengthening process. 2 O is a flux when the base glass is melted at high temperature, which can significantly reduce the melting temperature of the base glass. 2 When the O content is higher than 25%, the chemical stability of transparent glass-ceramics will be significantly reduced. 2 The molar content of O is less than or equal to 25%, which can keep the melting temperature within the appropriate range and ensure good ion exchange properties. 2The molar content of O is 12% to 25%, for example, Na 2 The molar content of O is 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, or any value in a numerical range consisting of any two of the above numerical values as endpoints, preferably 14% to 25%.
[0053] Li 2 O is an oxide with high alkali metal activity and is an external oxide of the glass network. As one of the additives to reduce the high temperature viscosity of the base glass, it can significantly improve the high temperature fluidity of the base glass. + In transparent glass-ceramics, ion exchange chemical strengthening reactions can be involved to further enhance the mechanical properties of glass-ceramics. 2 The molar content of O is 1% to 12%, for example, Li 2 The molar content of O is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12% or any value in a numerical range consisting of any two of the above numerical values as endpoints, preferably 2% to 10%.
[0054] MgO can improve the melting of transparent microcrystalline glass, lower the liquidus temperature, and have a good effect on improving the thermal stability of transparent microcrystalline glass. At the same time, MgO can improve the chemical stability and mechanical strength of transparent microcrystalline glass, and can reduce the crystallization tendency of transparent microcrystalline glass. However, when its content is too high, the crystallization performance of transparent microcrystalline glass is reduced, which is not conducive to obtaining the desired crystal phase type and grain size of microcrystalline glass. Therefore, the molar content of MgO in the microcrystalline glass component is 0% to 3%, for example, it can be 0%, 1%, 1.5%, 2%, 2.5%, 3% or any value in the numerical range composed of any two of the above values as endpoints.
[0055] ZrO 2 It is an intermediate oxide in the formation of transparent microcrystalline glass, which can improve the chemical stability of transparent microcrystalline glass, increase the hardness of transparent microcrystalline glass and its ability to resist scratches and drops. 2 The cationic charge of ZrO is high and the field is strong, which has a great accumulation effect on the transparent microcrystalline glass structure and is often used as a nucleating agent in transparent microcrystalline glass. 2 It will significantly increase the viscosity of the glass-ceramics and affect the forming ability of the glass-ceramics. 2 The molar content is 0% to 3%, for example, ZrO 2 The molar content is 0, 1%, 1.5%, 2%, 2.5%, 3% or any value in a numerical range consisting of any two of the above numerical values as endpoints.
[0056] B 2 O 3 As the external oxide of the network of microcrystalline glass, it is generally filled in the gaps of the silicon-oxygen tetrahedral framework. Its cation coordination rarely changes, and some properties of its oxide can be considered constant. 2 O 3 It helps to provide a base glass with a low melting temperature. In addition, adding B 2 O 3 , and can also improve the damage resistance of transparent microcrystalline glass. 2 O 3 The molar content is 0.5% to 6%, for example, B 2 O 3 The molar content is 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6% or any value in a numerical range consisting of any two of the above values as endpoints. Preferably, it is 0.5% to 5%.
[0057] P 2 O 5 It can be used as a nucleating agent in base glass and glass-ceramics to promote the phase separation and overall crystallization ability of base glass. 2 O 5 If the concentration is too low, the base glass will not crystallize, but will only form crystals from the surface to the inside at a higher temperature and lower viscosity. 2 O 5 If the concentration is too high, it will be difficult to control devitrification when cooling during the base glass formation process. 2 O 5 The molar content is 0.5-3%, for example, P 2 O 5 The molar content is 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or any value in a numerical range consisting of any two of the above numerical values as endpoints.
[0058] TiO 2 It is one of the nucleating agents for the nucleation and growth of crystals in glass-ceramics. It can effectively promote the growth of crystal nuclei in the process of nucleation and crystallization of base glass and improve the stability of glass. 2 The introduction of TiO 2 The introduction of TiO can easily cause phase separation in the base glass, leading to crystallization and affecting the formation of glass. 2 The molar content is 0% to 2%, for example, TiO 2The molar content is 0%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or any value in a numerical range consisting of any two of the above numerical values as endpoints.
[0059] SnO 2 , NaCl, Sb 2 O 3 As a good clarifier in the production of transparent microcrystalline glass, it can effectively homogenize the components of the precursor glass and reduce the formation of undesirable substances such as bubbles and stones. 2 , NaCl, Sb 2 O 3 The total molar content of one or more of the three is 0.1-2%, for example, the molar content of one or more of the three is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or any value in the numerical range consisting of any two of the above numerical values as endpoints. Preferably, it is 1% to 2%.
[0060] In the above embodiments, the B value in the optical color control LAB value of the transparent micro-ceramic glass satisfies 0.6≤|B value|≤1.0.
[0061] The above-mentioned transparent microcrystalline glass can be further chemically strengthened by ion exchange to improve the mechanical properties.
[0062] The present invention also provides a method for preparing the transparent glass-ceramics as described above in the present invention, which comprises the following steps:
[0063] S1. Mixing ingredients according to the components of transparent glass-ceramics to obtain a mixture;
[0064] S2, melting the mixed material, molding and annealing to obtain basic glass;
[0065] S3. The base glass is subjected to a nucleation treatment and a crystallization treatment in sequence to obtain the transparent microcrystalline glass.
[0066] In step S1, in some embodiments, the transparent glass-ceramics includes the following components in terms of molar percentage:
[0067] SiO 2 42%~65%,Al 2 O 3 10%~25%, Na 2 O 12%~25%, Li2 O 1%~12%, MgO0%~3%, ZrO 2 0%~3%, B 2 O 3 0.5%~6%, P 2 O 5 0.5%~3%, TiO 2 0% to 2%, clarifier (specific selection see above) 0.1% to 2%; and the sum of the molar percentages of each component is 100%.
[0068] Specifically, the ingredients are prepared according to this component.
[0069] In step S2, in some embodiments, the melting temperature is 1400-1650°C, for example, it can be 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, 1650°C or any value in a numerical range consisting of any two of the above values as endpoints.
[0070] In some embodiments, the base glass is formed by an overflow down-draw method, a float method, a casting method, or a roller pressing method, but is not limited thereto.
[0071] In some embodiments, the forming method includes one of overflow down-draw method, float method, casting method or roller pressing method, but is not limited thereto.
[0072] In some embodiments, the annealing temperature is 420-480°C, for example, it can be 420°C, 430°C, 440°C, 450°C, 460°C, 470°C or 480°C, or any value in a numerical range consisting of any two of the above values as endpoints; the annealing time is 6-24h, for example, it can be 6h, 8h, 10h, 12h, 15h, 18h, 20h, 22h, 24h, or any value in a numerical range consisting of any two of the above values as endpoints.
[0073] In step S3, in some embodiments, the temperature of the nucleation treatment is 500-600°C, for example, it can be 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C or any value in a numerical range consisting of any two of the above values as endpoints; the time of the nucleation treatment is 30-480min, for example, it can be 30min, 50min, 80min, 100min, 150min, 200min, 250min, 300min, 350min, 400min, 450min, 480min or any value in a numerical range consisting of any two of the above values as endpoints.
[0074] In some embodiments, the temperature of the crystallization treatment is 580-740°C, for example, it can be 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C or any value in a numerical range consisting of any two of the above values as endpoints; the time of the crystallization treatment is 10-240min, for example, it can be 10min, 30min, 50min, 80min, 100min, 150min, 200min, 240min or any value in a numerical range consisting of any two of the above values as endpoints.
[0075] The embodiment of the present invention further provides an application of the transparent microcrystalline glass as described above in the embodiment of the present invention in a consumer electronic product. Specifically, the transparent microcrystalline glass is used to prepare a protective cover plate of a display screen of a consumer electronic product.
[0076] In some embodiments, the consumer electronic product includes at least one of a mobile phone, a tablet computer, a POS machine, a smart wearable device, a display (specifically, a vehicle-mounted display), and a television. The vehicle-mounted display device screen can be installed on a car dashboard, a center console, behind the front seats, a rear console, a roof inside the car, etc.
[0077] The present invention will be further described below by means of specific examples.
[0078] Table 1. Formulas of transparent glass-ceramics in various embodiments and comparative examples
[0079]
[0080] Example 1
[0081] This embodiment provides a method for preparing a transparent microcrystalline glass, comprising the following steps:
[0082] (1) According to the components and proportions in Example 1 in Table 1, weigh 1000 g of each raw material powder, and then place it in a mixer and mix it for 30 minutes to obtain a mixture;
[0083] (2) transferring the above mixture into a platinum crucible, melting it at 1650°C for 5 hours, then pouring it into a molding mold for molding, cooling it to 900°C, annealing it in a 480°C annealing furnace for 12 hours, and then cooling it to room temperature at a rate of 5°C / min to obtain a basic glass;
[0084] (3) The base glass is placed in an annealing furnace and kept at 530°C for 4 hours for nucleation treatment, then heated to 641°C and kept at this temperature for 0.75 hours for crystallization treatment, and then cooled to room temperature with the furnace. After shaping, cutting, flat grinding and polishing, a transparent microcrystalline glass is obtained.
[0085] Example 2
[0086] This embodiment provides a method for preparing a transparent microcrystalline glass, which is different from the method in Embodiment 1 only in that: according to the components and proportions in Embodiment 2 in Table 1, 1000 g of each raw material powder is weighed;
[0087] In step (3), the temperature is kept at 591°C for 7 hours for nucleation treatment, and then the temperature is increased to 720°C and kept for 1 hour for crystallization treatment.
[0088] Example 3
[0089] This embodiment provides a method for preparing chemically strengthened glass-ceramics, which is different from the method of embodiment 1 only in that: according to the components and proportions in embodiment 3 in Table 1, 1000 g of each raw material powder is weighed;
[0090] In step (3), the temperature is kept at 532°C for 4 hours for nucleation treatment, and then the temperature is increased to 643°C and kept for 0.75 hours for crystallization treatment.
[0091] Example 4
[0092] This embodiment provides a method for preparing chemically strengthened glass-ceramics, which is different from the method in Embodiment 1 only in that: according to the components and proportions in Embodiment 4 in Table 1, 1000 g of each raw material powder is weighed;
[0093] In step (3), the temperature is kept at 566°C for 6 hours for nucleation treatment, and then the temperature is increased to 706°C and kept for 1 hour for crystallization treatment.
[0094] Example 5
[0095] This embodiment provides a method for preparing chemically strengthened glass-ceramics, which is different from the method in Embodiment 1 only in that: according to the components and proportions in Embodiment 5 in Table 1, 1000 g of each raw material powder is weighed;
[0096] In step (3), the temperature is kept at 523°C for 3 hours for nucleation treatment, and then the temperature is increased to 615°C and kept for 1.5 hours for crystallization treatment.
[0097] Example 6
[0098] This embodiment provides a method for preparing a chemically strengthened glass-ceramics, which is different from the method in the first embodiment only in that: according to the components and proportions in the first embodiment in Table 1, 1000 g of each raw material powder is weighed;
[0099] In step (3), the temperature is kept at 538°C for 3 hours for nucleation treatment, and then the temperature is increased to 635°C and kept for 0.5 hours for crystallization treatment.
[0100] Example 7
[0101] This embodiment provides a method for preparing chemically strengthened glass-ceramics, which is different from the method in Embodiment 1 only in that: according to the components and proportions in Embodiment 7 in Table 1, 1000 g of each raw material powder is weighed;
[0102] In step (3), the temperature is kept at 553°C for 6 hours for nucleation treatment, and then the temperature is increased to 657°C and kept for 1 hour for crystallization treatment.
[0103] Comparative Example 1
[0104] This comparative example provides a method for preparing a chemically strengthened glass-ceramics, which differs from Example 1 only in that: according to the components and proportions in Comparative Example 1 in Table 1, 1000 g of each raw material powder is weighed;
[0105] In step (3), the temperature is kept at 540°C for 6 hours for nucleation treatment, and then the temperature is increased to 648°C and kept for 1 hour for crystallization treatment.
[0106] The transparent microcrystalline glass in each embodiment was shaped, sliced, CNC (computer numerical control), flat ground and polished to obtain a transparent microcrystalline glass polished sheet with a thickness of 1 mm for testing:
[0107] (1) XRD test and Jade analysis
[0108] The glass-ceramics were ground into powder and analyzed by Rigaku Smartlab X-ray diffraction (XRD) test to analyze the crystal phase composition of the transparent glass-ceramics. Jade was used to analyze the crystal phase composition (types of the main crystal phase and the secondary crystal phase), the proportion of each crystal phase, the crystal size and the total crystallization degree. The results are as follows: Figure 1 And as shown in Table 2.
[0109] (2) Transmittance test
[0110] The light transmittance of the transparent microcrystalline glass polished sheets prepared in Examples 1-7 was tested using a Shimadzu UV-2600 ultraviolet visible spectrophotometer. The results are as follows: Figure 2 And as shown in Table 2.
[0111] (3) Haze test
[0112] The haze of the transparent microcrystalline glass polishing sheets prepared in Examples 1-7 was tested using a colorimeter (model CM-3600A, purchased from Konica Minolta, Japan). The results are shown in Table 2.
[0113] (4) LAB value test
[0114] The B values of the transparent glass-ceramics prepared in Examples 1-7 were tested and analyzed using a colorimeter (model CM-3600A, purchased from Konica Minolta, Japan). The results are shown in Table 2.
[0115] Table 2. Test results
[0116]
[0117] Among them, from the results of Example 3 and Example 7 compared with the results of Example 1, Example 2, Example 4, Example 5, Example 6 and Comparative Example 1, it can be seen that when the mass proportion of triclinic nepheline is greater than the mass proportion of sodium nepheline, the optical performance of the transparent microcrystalline glass is optimal. At the same time, if the content of the secondary crystalline phase is high, the overall optical performance will further decrease.
[0118] In summary, the present invention provides a transparent microcrystalline glass and a preparation method and application thereof. The haze of the transparent microcrystalline glass (when the thickness is ≤1.0 mm) is less than or equal to 0.15, the absolute value of the B value in LAB is between 0.6 and 1.0, and the average transmittance to light in the wavelength range of 400 to 780 nm is greater than or equal to 88%, and it has good optical properties.
[0119] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A transparent microcrystalline glass, characterized in that: The crystal phase of the transparent microcrystalline glass comprises a main crystal phase and a secondary crystal phase, the mass proportion of the secondary crystal phase in the transparent microcrystalline glass is greater than or equal to 0% and less than or equal to 8%; the average grain size of the secondary crystal phase is less than or equal to 10nm; the main crystal phase comprises sodium nepheline and triclinic nepheline, and the secondary crystal phase comprises sodium silicate and zirconium oxide; the total crystallinity of the transparent microcrystalline glass is greater than or equal to 20%; in the transparent microcrystalline glass, the average grain size of the crystal phase is greater than 10nm and less than or equal to 75nm; When the thickness of the transparent microcrystalline glass is less than or equal to 1.0 mm, the average transmittance of the transparent microcrystalline glass for light in the wavelength range of 400 to 780 nm is greater than or equal to 88%, and the haze of the transparent microcrystalline glass is less than or equal to 0.
15.
2. The transparent microcrystalline glass according to claim 1, characterized in that: In the transparent microcrystalline glass, the mass proportion of sodium nepheline in the crystal phase is greater than 50%, and the total crystallinity of the transparent microcrystalline glass is greater than or equal to 40% and less than or equal to 80%.
3. The transparent microcrystalline glass according to claim 1, characterized in that: In the transparent microcrystalline glass, the mass proportion of triclinic pyroxene in the crystal phase is greater than 50%, and the total crystallinity of the transparent microcrystalline glass is greater than 20% and less than or equal to 50%.
4. The transparent microcrystalline glass according to claim 1, characterized in that: The transparent glass-ceramics comprises the following components in terms of molar percentage: SiO2 42%~65%, Al2O3 10%~25%, Na2O 12%~25%, Li2O 1%~12%, MgO0%~3%, ZrO2 0%~3%, B2O3 0.5%~6%, P2O5 0.5%~3%, TiO2 0%~2%, clarifier 0.1%~2%; and the sum of the molar percentages of each component is 100%.
5. The transparent microcrystalline glass according to claim 4, characterized in that: The clarifier includes at least one of SnO2, NaCl and Sb2O3.
6. A method for preparing the transparent microcrystalline glass according to claim 1, characterized in that: The steps include: Mixing ingredients according to the components of transparent glass-ceramics to obtain a mixed material; After the mixture is melted, it is molded and annealed to obtain basic glass; The base glass is subjected to a nucleation treatment and a crystallization treatment in sequence to obtain the transparent micro-ceramic glass; Wherein, the transparent microcrystalline glass comprises the following components in terms of molar percentage: SiO2 42%~65%, Al2O3 10%~25%, Na2O 12%~25%, Li2O 1%~12%, MgO0%~3%, ZrO2 0%~3%, B2O3 0.5%~6%, P2O5 0.5%~3%, TiO2 0%~2%, clarifier 0.1%~2%; and the sum of the molar percentages of each component is 100%.
7. The preparation method according to claim 6, characterized in that: The temperature of the nucleation treatment is 500-600° C., and the time of the nucleation treatment is 30-480 minutes.
8. The preparation method according to claim 6, characterized in that: The temperature of the crystallization treatment is 580-740° C., and the time of the crystallization treatment is 10-240 minutes.
9. The preparation method according to claim 6, characterized in that: The forming method includes one of overflow down-draw method, float method, casting method or roller pressing method; The annealing temperature is 420-480° C., and the annealing time is 6-24 hours.
10. Application of the transparent microcrystalline glass according to any one of claims 1 to 5 in consumer electronic products.